2019
DOI: 10.1186/s40317-019-0183-5
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of small PIT-tagged animals using wildlife crossings

Abstract: Background: Mitigating the effect of linear transport infrastructure (LTI) on fauna is a crucial issue in road ecology. Wildlife crossing structures (tunnels or overpasses) are one solution that has been implemented to restore habitat connectivity and reduce wildlife mortality. Evaluating how these crossings function for small wildlife has often been recommended but, mainly due to technical limitations, is not often conducted in practice or only as short-term monitoring (less than 1 year). In this study, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…A monitoring system was designed, composed of four antennas (Biolog-id outdoor antennas, 100 × 8.5 × 2.5 cm), connected to an electronic control unit, described in detail in Testud et al (2019). Each antenna included an auto-tuning function and a rechargeable power battery.…”
Section: Design Of the Monitoring System And Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A monitoring system was designed, composed of four antennas (Biolog-id outdoor antennas, 100 × 8.5 × 2.5 cm), connected to an electronic control unit, described in detail in Testud et al (2019). Each antenna included an auto-tuning function and a rechargeable power battery.…”
Section: Design Of the Monitoring System And Experimentsmentioning
confidence: 99%
“…A study has also shown that acoustic enrichment of tunnels with frog calls increased the speed and complete crossing rates of water frogs (Pelophylax esculentus) and the great crested newt (Triturus cristatus) (Testud et al, 2020). Individuals with PIT tags tracked by RFID antennas deployed in tunnels can give detailed information on movements inside the tunnel (Testud et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Метод активно використовують для оцінювання ефективності ренатуралізації видів [20], дослідження їхнього поширення, пошуку кормових біотопів і оцінювання їхнього використання, швидкості росту, виживання [59], денної активності й характеру руху особин різної статі [65], під час оцінювання використання підземних захисних бар'єрів [63], пошуку нерестилищ або місць гібернації [1], використання особиною території проживання [43], під час боротьби з нелегальною торгівлею тваринами [17] тощо.…”
Section: вступunclassified
“…Radio-frequency identification (RFID) technology is of interest because electronic microchips using this technology (i.e., passive integrated transponder tags or PIT tags) do not require batteries or maintenance (Roberts, 2006;Want, 2006) and can be miniaturized. In ecology, these were first applied to fish (Prentice & Park, 1983) and then widely used to mark a plethora of taxa, including aquatic species, such as amphibians, for their identification and monitoring (Lucas & Baras, 2000;Roussel et al, 2000;Perret & Joly, 2002;Gibbons & Andrews, 2004;Schulte et al, 2007;Ferner, 2010;Testud et al, 2019). Several studies have concluded that this method has no detrimental effects on survival, growth, or body condition (Brown, 1997;Jehle & Hödl, 1998;Ott & Scott, 1999;Perret & Joly, 2002;Renet et al, 2021).…”
Section: Introductionmentioning
confidence: 99%